The 9-Anthroate chromophore as a fluorescent probe for water - Costa, Fernando Pestana da (2011)
Water quenches the fluorescence of methyl 9-anthroate with a rate constant showing little dependence on solvent viscosity or polarity. In dioxane, at 20ºC the value of the rate constant is 9.6 X 10^6 M^(-1) s^(-1) , and the activation energy found for the process is 14.1 kJ mol^(-1). The quenching process is entropy-controlled and is likely to involve a hydrogen-bonded complex as an intermediate. Since the fluorescence lifetime of methyl 9-anthroate does not depend on the solvent properties other than its hydrogen-bonding ability, the concentration of nearby water can be estimated directly. Values of 3, 54, and 14 M were obtained for the solubilization site of methyl 9-anthroate in micelles of Triton X-100, sodium dodecyl sulfate (SDS), and dodecyltrimethylammonium chloride (DTAC), respectively. From the ring current effect of the anthroate group on the 'H NMR chemical shifts of the surfactant protons, it is concluded that the anthroate fluorescent probe is preferentially located in the surface region of the SDS and DTAC micelles; however, in Triton X-100, it resides in the micelle interior near the phenoxy groups of the surfactant molecule.